1974
DOI: 10.1128/jb.117.3.1261-1269.1974
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Glucose, Gluconate, and Methyl α-D-Glucoside by Pseudomonas aeruginosa

Abstract: Glucose transport by Pseudomonas aeruginosa was studied. These studies were enhanced by the use of a mutant, strain PAO 57, which was unable to grow on glucose but which formed the inducible glucose transport system when grown in media containing glucose or other inducers such as 2-deoxy-D-glucose. Both PAO 57 and parental strain PAO transported glucose with an apparent Km of 7 ,uM. Free glucose was concentrated intracellularly by P. aeruginosa PAO 57 over 200fold above the external level. These data constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

1976
1976
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 15 publications
3
27
1
Order By: Relevance
“…In addition, D1 was not induced by a variety of different carbon sources (Table 1). Overall, the results demonstrated that under all conditions where the high affinity glucose uptake system and the periplasmic glucose binding protein were induced [1][2][3]11,12], protein D 1 was seen in SDS polyacrylamide gel electrophoretograms of outer membranes (Table 1). There was no such correlation between induction of protein D1 and the induction of the low affinity glucose uptake system [ 1,2], the mannitol, fumarate, glycerol or dicarboxylic acid uptake systems or a variety of hexose (including glucose) catabolizing enzymes [2,4,12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, D1 was not induced by a variety of different carbon sources (Table 1). Overall, the results demonstrated that under all conditions where the high affinity glucose uptake system and the periplasmic glucose binding protein were induced [1][2][3]11,12], protein D 1 was seen in SDS polyacrylamide gel electrophoretograms of outer membranes (Table 1). There was no such correlation between induction of protein D1 and the induction of the low affinity glucose uptake system [ 1,2], the mannitol, fumarate, glycerol or dicarboxylic acid uptake systems or a variety of hexose (including glucose) catabolizing enzymes [2,4,12].…”
Section: Resultsmentioning
confidence: 99%
“…N.D., not determined. c Taken from the data of [1][2][3]11,12]: + transport of glucose occurs by the indicated system; -, no transport of glucose; N.D., not determined.…”
Section: A O C O E Fmentioning
confidence: 99%
“…Active transport of glucose by P. aeruginosa, on the other hand, apparently is a shock-sensitive system because a glucose-binding protein has been detected (1 2). and because membrane vesicles prepared from P. aeruginosa were unable to actively transport glucose but they retained the ability to transport gluconate (3,4) and serine (unpublished observations). On the other hand, gluconate transport by P. aeruginosa apparently is shock resistant because membrane vesicles retained the ability to actively transport gluconate (3,4).…”
Section: Inhibitory Effect Of Pms-ascorbate On Active Transport Systemsmentioning
confidence: 93%
“…and because membrane vesicles prepared from P. aeruginosa were unable to actively transport glucose but they retained the ability to transport gluconate (3,4) and serine (unpublished observations). On the other hand, gluconate transport by P. aeruginosa apparently is shock resistant because membrane vesicles retained the ability to actively transport gluconate (3,4). When PMS-ascorbate was tested against these 2 transport systems of P. aeruginosa, both glucose and gluconate transport were found to be as extensively inhibited as proline transport.…”
Section: Inhibitory Effect Of Pms-ascorbate On Active Transport Systemsmentioning
confidence: 93%
See 1 more Smart Citation